2016
DOI: 10.1128/mcb.00723-15
|View full text |Cite
|
Sign up to set email alerts
|

High Fractional Occupancy of a Tandem Maf Recognition Element and Its Role in Long-Range β-Globin Gene Regulation

Abstract: c Enhancers and promoters assemble protein complexes that ultimately regulate the recruitment and activity of RNA polymerases. Previous work has shown that at least some enhancers form stable protein complexes, leading to the formation of enhanceosomes. We analyzed protein-DNA interactions in the murine ␤-globin gene locus using the methyltransferase accessibility protocol for individual templates (MAPit). The data show that a tandem Maf recognition element (MARE) in locus control region (LCR) hypersensitive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…We demonstrate the application of this assay to a systematically designed library of >1,500 promoter variants in yeast. In this assay, we utilize an approach previously used to interrogate several specific loci (Fatemi et al, 2005;Gal-Yam et al, 2006;Jessen et al, 2006;Kilgore et al, 2007;Small et al, 2014;Stees et al, 2015) or to measure mono-nucleosomes occupancy (as well as DNA methylation) genome-wide (Kelly et al, 2012;Taberlay et al, 2014). The method makes use of a methyltransferase that methylates accessible DNA, followed by bisulfite conversion ''recording'' the methylation status (indicative of the DNA occupancy) into the sequence.…”
Section: Introductionmentioning
confidence: 99%
“…We demonstrate the application of this assay to a systematically designed library of >1,500 promoter variants in yeast. In this assay, we utilize an approach previously used to interrogate several specific loci (Fatemi et al, 2005;Gal-Yam et al, 2006;Jessen et al, 2006;Kilgore et al, 2007;Small et al, 2014;Stees et al, 2015) or to measure mono-nucleosomes occupancy (as well as DNA methylation) genome-wide (Kelly et al, 2012;Taberlay et al, 2014). The method makes use of a methyltransferase that methylates accessible DNA, followed by bisulfite conversion ''recording'' the methylation status (indicative of the DNA occupancy) into the sequence.…”
Section: Introductionmentioning
confidence: 99%
“…The mouse LCR HS2 is formed in uninduced erythroid MEL cells as revealed by chromatin accessibility against DNase I or DNA methyltransferase and by transcription factor occupancy (Figure S4). 20,43 The deletion of human LCR HS2 from transgenic locus affected histone modifications at the human β‐globin promoter and gene body and LCR HS3 in hematopoietic progenitor cells, supporting the activity of HS2 as a seed enhancer in vivo 44 …”
Section: Discussionmentioning
confidence: 94%
“…16 We adopted this approach and previously demonstrated that 6 ZF-DBDs are useful tools for analyzing and modulating the function of cis-regulatory DNA elements in the mouse β-globin gene locus. 17,29,30 Expression of the β-type globin genes is modulated by many cis-and trans-regulatory components. 1,31 Re-expression of the normally silenced γ-globin genes has been shown to ameliorate the severity of phenotypes associated with thalassemia major and SCD.…”
Section: Discussionmentioning
confidence: 99%
“…ChIP was performed as described earlier. 30 Briefly, 5 × 10 7 cells were crosslinked with 1% (vol/vol) formaldehyde for 10 minutes at RT. Crosslinking was quenched by 125 mmol/l glycine.…”
Section: Zf-dbd Design and Constructionmentioning
confidence: 99%
See 1 more Smart Citation